Rebound effects flatten differences in carbon footprints between car-free households, minimal drivers, and green car owners - Juudit Ottelin; Sarah Olson; Vedant Ballal; Áróra Árnadóttir; Jukka Heinonen (Environmental Research Communications)
While the greenhouse gas emissions of most sectors are declining in the EU, transport emissions are increasing. Passenger cars compose a large share of the transport sector emissions, and a lot of effort has been made to reduce them. Despite the significantly improved environmental performance of passenger cars, there is a prevailing belief that they are the most environmentally harmful mode of ground transport. In the study at hand, we illustrate how rebound effects of consumption may change this view. Passenger car is a relatively expensive transport mode. Expenditure on car-ownership reduces the remaining household budget and the related carbon footprint. Here, we compare the total consumer carbon footprints per capita between fossil-fuel car owners, green car owners, and car-free households in the Nordic countries, using survey data including 7 400 respondents. When income and household type are controlled with regression analysis, respondents without a car for climate reasons and ‘minimal drivers’, meaning the least driving 10% of fossil-fuel car owners, have the lowest carbon footprints. Other car-free households have 6% higher footprints, electric- and biofuel car owners 18%–24% higher footprints, and the increasingly driving fossil-fuel car owners 30%–189% higher carbon footprints than the first two groups. However, the working middle-income green car owners, minimal drivers, and car-free households have very similar sized carbon footprints. The results show some trade-off between car ownership and flying despite that the data was collected between 2021 and 2022, when COVID-19 was still partly affecting air travel.